2017
DOI: 10.1088/1361-6579/aa8a1a
|View full text |Cite
|
Sign up to set email alerts
|

Improved ultrasound transducer positioning by fetal heart location estimation during Doppler based heart rate measurements

Abstract: The results show that the developed algorithm can be used to provide accurate feedback on fetal heart location for improved positioning of the US transducer, which may lead to improved measurements of the fHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In [20], the transmitted US beam profile of the same transducer elements used in the flexible array was characterized using a needle hydrophone (Precision Acoustics Ltd., Dorchester, UK). Here, we explicitly distinguished the US beam profile during transmit and receive mode.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [20], the transmitted US beam profile of the same transducer elements used in the flexible array was characterized using a needle hydrophone (Precision Acoustics Ltd., Dorchester, UK). Here, we explicitly distinguished the US beam profile during transmit and receive mode.…”
Section: Methodsmentioning
confidence: 99%
“…Due to reciprocity, the same characterization applies to the US beam in receive mode. Using experiments and simulations, it was shown that transmission with multiple elements, positioned in a rigid gird, leads to an US beam profile with multiple side lobes and interferences [20,28]. It should be noted that a group of seven concentrically arranged transducer elements (e.g., elements with index i = 1, i = 3, i = 4, i = 6, i = 8 and i = 9 in Figure 1b), corresponds to the array aperture of a commercially available US transducer [20,28].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations